EXPERIMENTAL CARDIOVASCULAR AND LUNG RESEARCHFrom mutation to methylation – molecular markers in lung cancer - Lewandowska, Marzena Anna; Grębicka, Katarzyna; Chrustek, Agnieszka; Kujawska, Ilona; Zaleska, Aleksandra; Kowalewski, Janusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Lung cancer is one of the most common types of malignant neoplasms in Poland and in the world, and is associated with the worst prognosis. Within recent years, significant progress has been made when it comes to high-throughput and high-resolution technologies in the field of molecular biology, i.e. next-generation sequencing, microarrays, and mass spectrometry, which contributed to the development of research in the fields of genomics, transcriptomics and epigenetics in lung cancer. Implementing the results achieved by these disciplines quickly allows for the analysis of somatic point mutations or translocations to be used in molecular cancer diagnostics, and, thus, for the personalization of treatment for patients with non-small cell lung cancer (NSCLC). Unfortunately, certain markers and prognostic predictors that could facilitate the detection of lung cancer in its early stages are yet to be found.